É a luta da gente! : juventude e etnicidade na comunidade Quilombola de capoeiras (RN) - Freire, Maíra Samara de Lima (2012)
On this paper, I propose a reflexion on the formation of a youth maroon, as a political subject , based on experience, personal expectations and social projects in the construction of a political identity in the community quilombola Capoeiras, which is located in the district of Macaíba (RN). I observed two social situations; the projects of the Pau-furado Youth and the Swingueira Quilombola , those kinds of dances that have as protagonists or as audience the youth people who lives in the community here mentioned, those people that legitimize and innovate in these traditions and roles they play and crucial positions in the construction of ethnic identities and generation within a political community. It seeks to understand the place of youth in this new context of political affirmation and identity. It is, therefore, to understand the diversity in their local youth from different social, cultural, political and economic